Hand eczema: treatment. (20th December 2019) - Elsner, P.; Agner, T.
Abstract: Hand eczema is a highly prevalent, multietiological disease with a wide spectrum of severity and chronicity. The treatment of hand eczema, especially in severe and chronic cases, is a challenge to the dermatologist requiring not only diagnostic and therapeutic, but also excellent patient communication skills. This review discusses the spectrum of therapeutic options for hand eczema, the evidence for their efficacy and safety, and proposes a stepwise approach of intensity of treatment depending on disease severity and chronicity. In the near future, hand eczema patients may benefit from new therapeutic principles such as biologics for the treatment of atopic eczema and topical Janus Kinase inhibitors.